Building on Traditional Medicinal Plant Knowledge and Home-Based Health Care Efforts in Rural Malawi - World Bank (Washington, DC, 2012)
Malawi remains one of the world's least developed countries, with more than 65 percent of its population of over 11 million below the poverty line. As in most countries in the region, biomedical health facilities and services are in very short supply, especially in the rural communities of Malawi-about 85 percent of its population. The HIV/AIDS epidemic has exacerbated the already strained scarce resources available within the national health delivery system. In the absence of adequate biomedical health services, most rural Malawians continue to rely on traditional, largely plant-derived treatments for their primary health care needs.